2015
DOI: 10.1590/0100-69912015004003
|View full text |Cite
|
Sign up to set email alerts
|

Night admission is an independent risk factor for mortality in trauma patients - a systemic error approach

Abstract: Night admission is an independent risk factor for mortality in Night admission is an independent risk factor for mortality in Night admission is an independent risk factor for mortality in Night admission is an independent risk factor for mortality in Night admission is an independent risk factor for mortality in trauma patients -a systemic error approach trauma patients -a systemic error approach trauma patients -a systemic error approach trauma patients -a systemic error approach trauma patients -a systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…It is interesting to note that the same country data might provide different results at the national, regional, and institutional levels. Our observations agree with Hirose's findings in Japan and others, such as the report by Barbosa et al, USA [29], who reported increased mortality during nights but not on weekends, similar to this cohort.…”
Section: Discussionsupporting
confidence: 94%
“…It is interesting to note that the same country data might provide different results at the national, regional, and institutional levels. Our observations agree with Hirose's findings in Japan and others, such as the report by Barbosa et al, USA [29], who reported increased mortality during nights but not on weekends, similar to this cohort.…”
Section: Discussionsupporting
confidence: 94%
“…Barbosa et al. 11 showed in their single-centre study involving 563 patients that mortality was higher among patients treated at night despite risk adjustment. No statement was made about injury severity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that this factor does not have an aggravating effect, 7 , 8 , 9 , 10 while others show that it has a negative influence. 11 , 12 , 13…”
Section: Introductionmentioning
confidence: 99%
“…Barbosa et al, for example, identified that operative trauma was more likely to occur at night, over the weekends, and was associated with greater mortality in their Brazilian trauma population. More specifically, they identified admission at night as an independent risk factor for surgical mortality in trauma patients [ 1 ]. Studies in the United Kingdom and Canada conversely found no difference in mortality between patients presenting on nights and/or weekends compared to those arriving at “normal” hours, which may reflect their highly developed multihospital acute care and trauma system [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the current literature is divided regarding the effect of time of day on trauma patient outcomes. Multiple countries including Japan, Canada, the United Kingdom, Germany, Brazil, and the United States have all performed retrospective studies using their trauma data banks over varied time frames attempting to confirm or refute the above belief [ [1] , [2] , [3] , [4] , [5] , [6] ]. However, none of these studies can agree if time of day truly impacts patient outcomes, and none have separated blunt from penetrating trauma.…”
Section: Introductionmentioning
confidence: 99%